KODIFIKASI HUKUM PIDANA NASIONAL PASCA-KOLONIAL: TELAAH LITERATUR ATAS UNDANG-UNDANG NOMOR 1 TAHUN 2023 DAN IMPLEMENTASINYA PADA JANUARI 2026 - Sunnah, Sunnah; Gunawan Widjaja (Prosiding Seminar Nasional Indonesia, 2025)
This study examines the codification of post-colonial national criminal law in Indonesia through a literature review of Law No. 1 of 2023 and its implementation, which is scheduled to come into effect in January 2026. Using a normative-legal literature review method, this study examines changes in the substance and philosophy of criminal law that reflect the values of Pancasila, human rights, and adaptation to social dynamics and technological developments. Additionally, this study highlights challenges in implementing the new Criminal Code, including the readiness of law enforcement officials, public awareness, and adjustments to the judicial and legal administrative systems. The findings indicate that the codification of criminal law through Law No. 1 of 2023 is a strategic step toward building a modern, sovereign, and just criminal legal system in Indonesia; however, the success of its implementation depends heavily on the synergy of all stakeholders and their readiness to adapt to change.